RANCANG BANGUN APLIKASI ENSIKLOPEDIA ELEKTRONIK TANAMAN OBAT BERBASIS ANDROID MENGGUNAKAN METODE LUTHER - Jadiaman Parhusip; Deddy Ronaldo; Bagus Valentino (Universitas Palangka Raya, 2020)
This Design of android-based application of electronic encyclopedia of medicinal plant was created as a way to provide information to people about the benefits of herbal medicinal plants.This application used the website as the site admin to enter data of medicinal plants and the application (android) as a place for users to view information of medicinal plants. The software engineering design was Luther method. This method is also called Multimedia Development Life Cycle which is a model developed through 6 stages; Concept, Design, Material Collecting, Assembly, Testing, and Distribution. This Luther model has similar stages to Waterfall model so it can be easily understood and implemented, easy to follow and can be used by small developers. The result of this application was hoped to help users to know which herbal plant that can be made into medicine that can cure some specific diseases.